Multi‐method assessment of irritability and differential linkages to neurophysiological indicators of attention allocation to emotional faces in young children. Issue 5 (20th October 2019) - Deveney, Christen M.; Grasso, Damion; Hsu, Amy; Pine, Daniel S.; Estabrook, Christopher R.; Zobel, Elvira; Burns, James L.; Wakschlag, Lauren S.; Briggs‐Gowan, Margaret J.
Abstract: Facilitated attention toward angry stimuli (attention bias) may contribute to anger proneness and temper outbursts exhibited by children with high irritability. However, most studies linking attention bias and irritability rely on behavioral measures with limited precision and no studies have explored these associations in young children. The present study explores irritability‐related attention biases toward anger in young children ( N  = 128; ages 4–7 years) engaged in a dot‐probe task with emotional faces, as assessed with event‐related brain potential (ERP) indices of early selective attention and multi‐method assessment of irritability. Irritability assessed via semi‐structured clinical interview predicted larger anterior N1 amplitudes to all faces. In contrast, irritability assessed via a laboratory observation paradigm predicted reduced P1 amplitudes to angry relative to neutral faces. These findings suggest that altered early attentional processing occurs in young children with high irritability; however, the nature of these patterns may vary with methodological features of the irritability assessments. Future investigations using different assessment tools may provide greater clarity regarding the underlying neurocognitive correlates of irritability. Such studies may also contribute to the ongoing debates about how to best define and measure irritability across the developmental spectrum in a manner that is most informative for linkage to neural processes.